LITERASI KEUANGAN MASYARAKAT TENTANG PERBANKAN SYARIAH: SEBUAH PENDEKATAN MANAJEMEN PEMASARAN - Iwan Kusnadi; Maria Maria (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
Indonesia, which consists of various types of banks, both conventional and sharia banks, has their own approach to promotions to their customers, including the Sambas branch of the Kalbar Syariah bank. However, among the promotions carried out by Bank Kalbar Syariah there are efforts and efforts to promote the bank to the Sambas community, even though there are obstacles.